Engaging Audiences with Courtesy: Gender Differences in Positive Politeness Strategies within TED Educational Speech videos - Sangaji, Fahmi Arif; Hendi Pratama; Sri Wuli Fitriati (English Education Journal, 2024)
Improper communication, such as insults or bad language, is a communication problem. It may harm or threaten others in various situations. Positive politeness strategy can be used as the communication strategy to avoid face-threatening acts (FTA) and make the interlocutors feel comfortable. We examined positive politeness strategies used by male and female speakers in educational TED Talks speech videos and explained the differences between male and female speakers on the use of positive politeness. The strategies were analyzed using Brown and Levinson's (1988) politeness theory. This study used discourse analysis with pragmatic approach. Data was obtained from four educational TED Talks speech videos with two male and two female speakers. There were several stages to analyze the data using discourse study, including data identification, data categorization, data interpretation, conclusion drafting and verification. The findings suggest that male speakers often giving or asking for reasons in speeches to explain why they did it. Women often joked in their speeches to relaxed audiences and put them at ease. Also, joking strategy were applied differently by male and female speakers in delivering speeches. The female speaker had to explain the contexts and describe the images, whereas the male speaker was more spontaneous and fun. The findings of this study showed how male and female speakers use the appropriate utterances when delivering their speech in front of the audiences. Positive politeness strategies are used by the speakers to show their interest, build togetherness, and avoid conflict. Besides, the findings of this study can show the speakers’ ability in pragmatic competence by looking at their language use in specific context.